1998
DOI: 10.1177/107110079801900808
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Sesamoid Subluxation: How Good Is the AP Radiograph?

Abstract: Subluxation of the metatarsosesamoid joints frequently occurs with the development of hallux valgus deformity, and the restoration of a normal metatarsosesamoid articulation has been proposed as essential for achieving a biomechanically sound operative result. The position of the sesamoid bones on the AP radiograph is used often to assess the pre- and postoperative relationship between the hallucal sesamoids and the metatarsal sulci. We evaluated the validity of this approach. Thirty subjects with hallux valgu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 14 publications
2
56
0
3
Order By: Relevance
“…This result is consistent with the studies by Inman (20), Talbot and Saltzman (21), and Dayton et al (13,14), which showed a pronated metatarsal will increase the sesamoid position on anteroposterior radiographs. In conjunction with the work by Okuda et al (6,12,18) and Grode and McCarthy (1), we advance the idea that the sesamoid position, lateral rounding of the metatarsal head, and the appearance of a medial eminence are effective indicators of the rotational position in the assessment, correction, and follow-up of patients with bunion deformities.…”
Section: Discussionsupporting
confidence: 94%
“…This result is consistent with the studies by Inman (20), Talbot and Saltzman (21), and Dayton et al (13,14), which showed a pronated metatarsal will increase the sesamoid position on anteroposterior radiographs. In conjunction with the work by Okuda et al (6,12,18) and Grode and McCarthy (1), we advance the idea that the sesamoid position, lateral rounding of the metatarsal head, and the appearance of a medial eminence are effective indicators of the rotational position in the assessment, correction, and follow-up of patients with bunion deformities.…”
Section: Discussionsupporting
confidence: 94%
“…They recommended taking measurements from tangential radiographs using the Walter-M€ uller view. Some investigators have agreed with them (22,25); however, the Walter-M€ uller view requires dorsiflexion of the MTPJ (1,25,29), which moves the sesamoid complex distally and dorsally.…”
Section: Discussionmentioning
confidence: 96%
“…Currently, some surgeons have questioned just how best to determine the position of the sesamoid complex, and some have studied the relationship between the first metatarsal head and the sesamoid complex (21,23,29,40). Talbot and Saltzman (29) reported a discrepancy in the measurements between anteroposterior and tangential simple radiographs in 50% of 60 cases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The medial sesamoid was chosen instead the 1 st metatarsal head because it is regularly closer to the foot sole / ground. The medial sesamoid was chosen instead of the lateral sesamoid because it is less likely to completely dislocate from underneath the 1 st metatarsal head in forefoot deformities such as hallux valgus [23,25].…”
Section: Measurements Of Bone Position (Angles and Distances)mentioning
confidence: 99%